Taṭbīq al-Ta’līm al-Syumūlī fī Ta’līm al-Lugah al-‘Arabiyah bi al-Madrasah al-Mutawassiṭah - Rahmah, Zuherini; Harisca, Rodhi; Fatarib, Husnul (Study Program of Arabic Language Teaching, 2024)
This research aims to explore the application of holistic learning in Arabic language learning at Muhammadiyah Ahmad Dahlan Middle School, Metro Lampung. The main focus of this research is to understand how a holistic approach can improve students' Arabic language understanding and skills, as well as identifying factors that support and hinder its implementation. This research uses a qualitative methodology with a case study approach. Data was collected through classroom observations, in-depth interviews with teachers and students, as well as analysis of documents related to the curriculum and teaching materials. This approach allows researchers to get an in-depth picture of learning processes and experiences in the field. The research results show that the application of holistic learning in Arabic language learning at this school has had a positive impact on increasing students' understanding and language skills. Students show greater interest and more active participation in the learning process. However, research also found several obstacles, such as limited resources and lack of training for teachers.